2001
DOI: 10.1063/1.1350624
|View full text |Cite
|
Sign up to set email alerts
|

Critical cooling rate and thermal stability of Zr–Ti–Cu–Ni–Be alloys

Abstract: The critical cooling rate as well as the thermal stability are measured for a series of alloys in the Zr-Ti-Cu-Ni-Be system. Upon cooling from the molten state with different rates, alloys with compositions ranging along a tie line from (Zr 70 Ti 30 ) 55 (Ni 39 Cu 61 ) 25 Be 20 to (Zr 85 Ti 15 ) 55 (Ni 57 Cu 43 ) 22.5 Be 27.5 show a continuous increase in the critical cooling rate to suppress crystallization. In contrast, thermal analysis of the same alloys shows that the undercooled liquid region, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 158 publications
(77 citation statements)
references
References 17 publications
6
69
1
1
Order By: Relevance
“…In both cases, a strong dependence of ⌬T and d c on the composition variations can be observed. However, no obvious correlation between ⌬T and d c , as previously reported to be positive 22,23 or negative, 20,24 was observed.…”
contrasting
confidence: 53%
“…In both cases, a strong dependence of ⌬T and d c on the composition variations can be observed. However, no obvious correlation between ⌬T and d c , as previously reported to be positive 22,23 or negative, 20,24 was observed.…”
contrasting
confidence: 53%
“…18 Though peaks at positions corresponding to the quasicrystalline phase are still present as well, it cannot be unambiguously determined whether the quasicrystalline phase remains after the second crystallization event. There is a difference between the alloys in the types of 15 Because each sample is already partially crystallized before the constant heating rate measurement used to measure T g , the endothermic heat-flow signal during the glass transition is smaller in magnitude and it is more difficult to determine the onset, resulting in the substantial scatter shown.…”
Section: Resultsmentioning
confidence: 99%
“…The hightemperature crystallization behavior ͑above the isothermal annealing temperature at which crystallization is most rapid͒ for this alloy series has also been explored previously. 15 In this case, crystallization upon cooling at a constant rate resulted in the determination of the critical cooling rate R c , and measurements revealed that R c is lowest for Vit1͑-b͒-Vit1, i.e., these alloys are the best glass formers in the series. FIG.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations